3-(1, 1, 2, 2-Tetrafluoroethoxy)-1, 1, 2, 2-tetrafluoropropane as a High Voltage Solvent for LiNi1/3Co1/3Mn1/3O2/Graphite Cells. Issue 10 (1st January 2015) - Wang, Chengyun; Tang, Sihan; Zuo, Xiaoxi; Xiao, Xin; Liu, Jiansheng; Nan, Junmin
Abstract : A new electrolyte based on fluorinated 3-(1, 1, 2, 2-tetrafluoroethoxy)-1, 1, 2, 2-tetrafluoropropane (F-EPE) solvent is developed to decrease the capacity fading of LiNi1/3 Co1/3 Mn1/3 O2 /graphite lithium-ion batteries (LIBs) cycled in the voltage range of 3.0–4.5 V (vs. Li/Li + ). The linear sweep voltammetry (LSV) and cyclic voltammetry (CV) indicate that F-EPE has an oxidation potential of more than 5.4 V vs. Li/Li +, which is higher than traditional solvents and enlarges the oxidative window of electrolyte. Especially, compared with the LiNi1/3 Co1/3 Mn1/3 O2 /graphite cells without F-EPE in the electrolyte, the capacity retentions of the cells contained 20 wt% F-EPE and cycled in 3.0–4.5 V are significantly increased from 12.3% to 85.0% after 100 cycles. In addition, the cathode and the anode are respectively characterized in three-electrode systems by electrochemical impedance spectrum (EIS), scanning electron microscope (SEM), energy dispersive spectrometer (EDS), and transmission electron microscopy (TEM) to elaborate the reaction mechanism of F-EPE in the cells. The enhanced performances can be ascribed to that F-EPE cannot only greatly improve the oxidation stability of electrolyte solutions but also participate in the formation of passivation film on the graphite anode, indicating the positive effect of F-EPE on the performances of LIBs cycled in 3.0–4.5 V.